2000
DOI: 10.5014/ajot.54.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Father–Infant Interactions Using the NCAST Teaching Scale: A Pilot Study

Abstract: There may be important differences in the interactions of father-infant dyads compared with mother-infant dyads, but further research with a larger, more representative sample of fathers on this parent-infant interaction measure is warranted to support this. The development of normative scores for fathers and their infants is recommended to accurately interpret father-infant interactions when administering the NCAST Teaching scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
(10 reference statements)
1
13
0
Order By: Relevance
“…In the literature on TD children, fathers (compared to mothers) are often depicted as less sensitive (Lamb, Frodi, Frodi, & Hwang, 1982;Nakamura, Stewart, & Tatarka, 2000), if more active and fun playmates (Caneva & Venuti, 1998;Hewlett, 1992;Lamb, 1977Lamb, , 2004Notaro & Volling, 1999;Parke, 1996;Venuti & Giusti, 1996). Only two existing studies that specifically aimed to compare parents with regard to EA have also confirmed this idea (Lovas, 2005;Volling et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…In the literature on TD children, fathers (compared to mothers) are often depicted as less sensitive (Lamb, Frodi, Frodi, & Hwang, 1982;Nakamura, Stewart, & Tatarka, 2000), if more active and fun playmates (Caneva & Venuti, 1998;Hewlett, 1992;Lamb, 1977Lamb, , 2004Notaro & Volling, 1999;Parke, 1996;Venuti & Giusti, 1996). Only two existing studies that specifically aimed to compare parents with regard to EA have also confirmed this idea (Lovas, 2005;Volling et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Some of the popular stereotypes include "fathers are less involved in the parenting tasks" and "mothers maintain a better relationship with the children than fathers". Empirically, there are research findings in infancy and childhood showing that mothers are more involved than fathers in the socialization process and mothers maintain a closer relationship with their children than fathers (e.g., Nakamura et al 2000). Theoretically, there are several non-mutually exclusive accounts of the relatively higher parenting involvement of mothers relative to fathers.…”
Section: Introductionmentioning
confidence: 94%
“…The few studies that have actually compared mothers and fathers on the same measures have yielded mixed results (e.g., Braungart-Rieker, Garwood, Powers, & Notaro, 1998;Nakamura, Stewart, & Tatarka, 2000). We thus have no clear idea how fathers' interactions with their infants might play into this emerging picture of early gender development.…”
mentioning
confidence: 91%
“…Some researchers, comparing mothers and fathers on the same instruments, have found fathers to be less sensitive or responsive than mothers (e.g., Nakamura et al, 2000). In addition, there is a life-span female advantage in the decoding of social and emotional nonverbal communication (Brody, 1985;Halpern, 1992;Haviland & Malatesta, 1981), which is a necessary skill for EA and optimal structuring (Biringen et al, 1998).…”
Section: Parent Gender Differencesmentioning
confidence: 99%